2020
DOI: 10.1186/s12942-020-00243-z
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the association of objective and perceived neighborhood environment with physical activity in older adults: challenges and implications from a systematic review

Abstract: Background A supportive environment is a key factor in addressing the issue of health among older adults. There is already sufficient evidence that objective and self-reported measures of the neighborhood environment should be taken into account as crucial components of active aging, as they have been shown to influence physical activity; particularly in people aged 60+. Thus, both could inform policies and practices that promote successful aging in place. An increasing number of studies meanwh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 163 publications
(282 reference statements)
2
48
0
1
Order By: Relevance
“…Low agreement between the perceived and objective availability measures confirmed that these two measures captured different aspects of local green and blue spaces and their relevance for people with dementia. While this study focused on people with mild-to-moderate dementia, the results correspond to the large body of previous quantitative research on healthy adults and older people, which has reported inconsistency between perceived and objective environmental measures and different relationships with physical activity and walking [34][35][36], mental health [37] and health-related quality of life [38]. This demonstrates that although people with dementia may have memory problems and difficulties with orientation, variation between perceived and objective environmental measures is likely to be observed in both those with and without dementia.…”
Section: Interpretation Of Findingssupporting
confidence: 80%
“…Low agreement between the perceived and objective availability measures confirmed that these two measures captured different aspects of local green and blue spaces and their relevance for people with dementia. While this study focused on people with mild-to-moderate dementia, the results correspond to the large body of previous quantitative research on healthy adults and older people, which has reported inconsistency between perceived and objective environmental measures and different relationships with physical activity and walking [34][35][36], mental health [37] and health-related quality of life [38]. This demonstrates that although people with dementia may have memory problems and difficulties with orientation, variation between perceived and objective environmental measures is likely to be observed in both those with and without dementia.…”
Section: Interpretation Of Findingssupporting
confidence: 80%
“…m. UGS per capita. The benefits of UGS have been widely documented, however, a majority of the findings are from HICs [ 6 , 20 , 21 ]. This limits the generalizability of the evidence to LMICs and there is minimal research exploring the influence of UGS on ageing in India.…”
Section: Introductionmentioning
confidence: 99%
“…Features of the built environment, such as transport, pathways, access to shops and amenities, were reported in our study to be important to older people, as they largely determine the opportunities to avail of these services. Interactions with the environment are increasingly important for older people as they spend more and more time in their own home, through retirement, or for health reasons [ 15 ]. Agency, or the capacity of older adults to make choices about important aspects of their lives, is strongly impacted by the ability to access and avail of local services and maintain social connections.…”
Section: Discussionmentioning
confidence: 99%